The Teaching Portfolio; The Handbook of Technical Writing: Form and Style; Technical Writing: A Reader-Centered Approach ; Learning to Use Simplified English: A Preliminary Study - Debrah H. Jefferson; Robert G. Hays; Carol Sanders Reiner (Journal of Applied Communications, 1992)
Book and article reviews of The Teaching Portfolio, by Peter Seldin; The Handbook of Technical Writing: Form and Style, by Mary Lee, Gloria Stephenson, Max Anderson and Lynn Allen Lee; and Technical Writing : A Reader Centered Approach, by Paul V. Anderson; Learning to Use Simplified English: A Preliminary Study, Margaret Thomas, Gloria Jaffe, J. Peter Kincaid and Yvette Stees in Technical Communication;